Thermal Degradation of Single-Walled Carbon Nanotubes during Alcohol Catalytic Chemical Vapor Deposition Process - Mohd Abid, Mohd Asyadi Azam (Japan Society of Applied Physics, 2010)
We have grown single-walled carbon nanotubes (SWCNTs) from Co catalyst thin films using the alcohol catalytic chemical vapor deposition (CVD) method for different CVD processing times. The structural properties of the SWCNTs grown have been investigated by Raman spectroscopy with various laser excitations. The growth progressed up to t = 20 min, but the Raman intensity of SWCNTs decreased with increasing CVD processing time. The quality of as-grown SWCNTs also decreased with increasing CVD processing times, similar to the trend for Raman intensity. Raman intensity analysis in the radial breathing mode (RBM) region shows a relatively wide distribution for SWCNTs grown for all CVD processing times, owing to the variations in growth and burning rates with SWCNT diameter. In this paper, we suggest that Co catalyst poisoning and SWCNT burning occur when the CVD processing time is more than 20 min.